(untitled) ("Journal "U". Economy. Management. Finance.", 2024)
The article considers the evaluation of activities through periodic employee evaluations. The importance of certification is shown as a necessary stage in the cycle of managing the organization’s activities and evaluating the results of work. The methods, features and nuances of conducting certification interviews are given. The structure of the certification interview and an example of a typical interview schedule are described in detail. The benefits of the parties from a well-prepared and conducted certification interview are shown